Social Emotional Competence, Learning Outcomes, Emotional and Behavioral Difficulties of Preschool Children: Parent and Teacher Evaluations - Martinsone, Baiba; Supe, Inga; Stokenberga, Ieva; Damberga, Ilze; Cefai, Carmel; Camilleri, Liberato; Bartolo, Paul; O’Riordan, Mollie Rose; Grazzani, Ilaria (Frontiers in Psychology, 2022)
This paper addresses the role of social emotional competence in the emotional and behavioral problems and learning outcomes of preschool children based on their parents’ and teachers’ evaluations. In this study, we compared the perceptions of teachers and parents when evaluating the same child using the multi-informant assessment. First, the associations and differences between both the informant evaluations were investigated. Second, the correlation of the social emotional competence and emotional, and behavioral difficulties among preschool children was analyzed, separately addressing their parents’ and teachers’ evaluations. Third, the role of the preschool children’s social emotional competence in their emotional and behavioral problems, and learning outcomes was investigated building the regression and mediation models. The sample consisted of 507 preschool children (3–6 years, mean age 4.85 years, SD 0.82) and their parents and teachers. Both informants completed the Strengths and Difficulties Questionnaire and Social Skills Improvement System Social-Emotional Learning Brief Scales, and teachers reported on each child’s learning outcomes (by completing a three-item Learning outcomes measure). When comparing both informants’ evaluations, positive associations were found between teacher and parental evaluations of prosocial behavior and emotional, and behavioral difficulties of preschool children, as well as self-management. Parents evaluated their children higher than teachers in conduct problems, hyperactivity, prosocial behavior, and total difficulty, while teachers evaluated children higher than parents in social emotional competence. According to teachers, the social emotional competence of preschool children was negatively correlated to all difficulty scales, and positively related to the prosocial behavior scale. The demographic variables, as well as parental socioeconomic status and children’s belonging to a vulnerable group were not found to be significantly associated with the preschool children’s learning outcomes. However, social emotional competence remains a significant variable in teacher-rated learning outcomes of preschool children even if sociodemographic variables are controlled. Our findings indicate that a higher level of social emotional competence and lower levels of social, emotional, and behavioral difficulties are related to a higher preschoolers’ academic learning in their teachers’ evaluation. This suggests the importance of early facilitation of social emotional competence as a key factor for academic success and more positive behavioral outcomes.